Sensitive Determination and Pharmacokinetic Study of Amlodipine in Human Serum by LC-ESI/MS/MS - Li, N.; Xu, Y.; Luo, Y.N.; Sun, J.J.; Zhai, Y.Y.; Guo, Q.X. (Asian Journal of Chemistry, 2012)
A sensitive LC-ESI/MS/MS method was developed and validated to determine the concentrations of amlodipine in human serum. Amlodipine and the internal standard (IS) omeprazole were extracted from 200 μL of human serum by liquid-liquid extraction, using ethyl acetate as the extraction solvent. Sample analysis was performed by reversed-phase LC-MS/MS with electrospray ionization in positive ion mode, using selected reaction monitoring. The mobile phase composed of methanol and 0.15 % ammonium acetate in water (78 : 22, v/v) at a flow rate of 0.2 mL/min. The linearity ranged from 0.2 to 12.8 ng/mL. The extraction recoveries of amlodipine ranged from 90.68 to 105.27 %. The method was successfully used to pharmacokinetic study of amlodipine after an oral administration of 10 mg amlodipine tablets to 19 healthy volunteers.